Predictors of empowerment in parents of children with autism and related neurodevelopmental disorders who are undergoing genetic testing - Iskra Peltekova (Wiley, 2021)
Abstract Background There is limited empirical data quantifying the utility of genetic testing for families of children with autism spectrum disorder (ASD) or related neurodevelopmental disorders (NDD). We assessed the utility of clinical chromosomal microarray analysis (CMA), defined by diagnostic yield and parental empowerment, in population‐based sample of parents of affected children; and explored child, family, and health services factors predictive of empowerment. Methods Participants were families of children undergoing diagnostic assessments, between 2016 and 2019. Diagnostic yield of CMA in affected children was determined. Parental empowerment was measured through adapted version of the Genetics Counseling Outcome Scale‐24. Parents completed questionnaires to capture child, family, and health service factors. Results The diagnostic yield of CMA was 2.8% for pathogenic variants. Parental empowerment was significantly correlated with family functioning and aspects of perceived family‐centeredness of care. The model accounted for 49.8% of the variation in parental empowerment, F (10,37) = 3.67, p = 0.002. After accounting for other predictors, parental perception of the provision of general information remained significantly associated with empowerment. Conclusion The informational needs of families play an important role in their empowerment during genetic testing. Meeting these needs and monitoring empowerment can aid genomic technologies integration in personalized healthcare for ASD/NDD.